Control interno en una asociación hospitalaria - González Mejía, Silvana Lissette (2021)
The objective of the research is to propose a systematization model regarding internal controls, guaranteeing the performance of operational and financial processes in the Hospital Association, in order to establish a system linked to internal control according to the collection financial area. A theoretical framework was determined according to the definitions, principles, characteristics, importance, objectives and components of internal control and then focused on the institution. The methodology incorporated a type of documentary, non-experimental, descriptive research, on which tools such as the observation file, financial analysis, interviews were included to later obtain results in which it was concluded that the most serious problem was in unpaid accounts of the Ecuadorian Institute of Social Security. It was concluded that corrective actions should be implemented based on a proposal made and it was recommended to follow these corrective measures by means of a more pertinent definition and delimitation of functions, or the medium-term subsistence of the hospital association would be put at risk..........